Quality Culture in Higher Education Institutions in Nepal: Experiences and Perceptions of Students, Teaching and Non-Teaching Staff - Sapkota, Tikaram (Academia Journal of Humanities & Social Sciences, 2025)
Most educationists believe that fostering a culture of quality within higher education institutions (HEIs) is essential for overall development of HEIs. This statement is relevant to higher education institutions in Nepal. Thus, the objective of this paper is to examine the quality culture practices at Myagdi Multiple Campus (MMC), Beni Bazaar, Nepal. The study primarily utilized a quantitative research approach, employing a descriptive research design and organizational culture theory to examine the shared values, beliefs, and behaviors within the HEIs. A sampling survey method was used gathering responses from 69 respondents, including students, teaching and non-teaching staff, through online survey such as collecting data through Google forms. This method involved a thorough exploration of individual experiences and perspectives concerning the current quality culture practices in the campus. The study concluded that while certain aspects of the quality culture were well established, there was a need for continuous improvement in the areas such as open and transparent communication, careful planning, and stakeholder engagement. These areas received mixed or lower ratings, indicating that the respondents identified them as needing further development. Hence, the campus should focus on increasing recognition of its programs, strengthening faculty development, and addressing areas that received mixed feedback.